Un’interrogazione costante sul senso della storia (Materiali di Estetica. Terza serie, 2016)
By an overview, the essay analyzes Guido D. Neri’s works concerning philosophy of history that, although partial, are a very important aspect of his overall work. Primarily here are summed up his remarks on the meaning of history and on a new concept of praxis that overtakes his historical materialism. Very original is the query starting point about history meaning founded on the phenomenology of perception. In these works appear privileged speakers, such as Antonio Banfi, Kosìk, Patočka, Merleau-Ponty, H. Arendt, who together cover a period of forty years. Complementary to the theoretical thinking, there is the more analytical critical reflection, sometimes focused directly on some of the greatest historical and political events to the late 20th century: the Prague Spring, the Polish movement Solidarność, the Est European communist contradictions, the cultural Europe role return, the end- of-century genocides. Neri shows an acute sensitivity grasping signs of the new.